Impact of US Brown Swiss genetics on milk quality from low-input herds in Switzerland: Interactions with grazing intake and pasture type. (15th May 2015) - Stergiadis, S.; Bieber, A.; Franceschin, E.; Isensee, A.; Eyre, M.D.; Maurer, V.; Chatzidimitriou, E.; Cozzi, G.; Bapst, B.; Stewart, G.; Gordon, A.; Butler, G.
Highlights: Breeding by feeding interactions in milk quality were studied on low-input dairy farms. Crossbreeding with traditional breeds did not affect milk yield from low-input systems. Grazing natural pastures improved milk fatty acid profile. Omega-3 content was maximised by combining traditional genetics with high grazing diets. Abstract: This study investigated the effect of, and interactions between, contrasting crossbreed genetics (US Brown Swiss [BS] × Improved Braunvieh [BV] × Original Braunvieh [OB]) and feeding regimes (especially grazing intake and pasture type) on milk fatty acid (FA) profiles. Concentrations of total polyunsaturated FAs, total omega-3 FAs and trans palmitoleic, vaccenic, α-linolenic, eicosapentaenoic and docosapentaenoic acids were higher in cows with a low proportion of BS genetics. Highest concentrations of the nutritionally desirable FAs, trans palmitoleic, vaccenic and eicosapentaenoic acids were found for cows with a low proportion of BS genetics (0–24% and/or 25–49%) on high grazing intake (75–100% of dry matter intake) diets. Multivariate analysis indicated that the proportion of OB genetics is a positive driver for nutritionally desirable monounsaturated and polyunsaturated FAs while BS genetics proportion was positive driver for total and undesirable individual saturated FAs. Significant genetics × feeding regime interactions were also detected for a range of FAs.